A GOAL QUESTION METRIC (GQM) APPROACH FOR EVALUATING INTERACTION DESIGN PATTERNS IN DRAWING GAMES FOR PRESCHOOL CHILDREN - Dana Sulistiyo Kusumo; Mira Kania Sabariah; Kemas Rahmat Saleh Wiharja (Jurnal Ilmu Komputer dan Informasi, 2017)
In recent years, there has been an increasing interest to use smart devices’ drawing games for educational benefit. In Indonesia, our government classifies children age four to six years old as preschool children. Not all preschool children can use drawing games easily. Further, drawing games may not fulfill all Indonesia's preschool children’s drawing competencies. This research proposes to use Goal-Question Metric (GQM) to investigate and evaluate interaction design patterns of preschool children in order to achieve the drawing competencies for preschool children in two drawing Android-based games: Belajar Menggambar (in English: Learn to Draw) and Coret: Belajar Menggambar (in English: Scratch: Learn to Draw). We collected data from nine students of a preschool children education in a user research. The results show that GQM can assist to evaluate interaction design patterns in achieving the drawing competencies. Our approach can also yield interaction design patterns by comparing interaction design patterns in two drawing games used.